ENGLISH TEACHERS’ STRATEGY PREFERENCES IN ENGLISH CLASSES IN SMAN 1 TEJAKULA - Dewi, Luh Lingga; Luh Putu Artini; Dewa Ayu Eka Agustini (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to obtain the preference of teaching strategies most frequently used by male and female English teachers at SMAN 1 Tejakula. The teaching strategies recommended by Merdeka Curriculum were the focus of this study. Through a qualitative method, data collection was conducted using 3 different instruments: teaching strategy checklist, observation checklist, and interviews. There were 4 subjects involved in this study: 2 male teachers and 2 female teachers. The findings showed that male teachers showed a preference for the Problem-Based Learning teaching strategy based on the grade level they taught. On the other hand, female teachers showed a tendency towards a combination of Project-Based Learning and Discovery Learning teaching strategies due to the ability or character of the students themselves and the grade level being taught. A unique thing was also found in this study, where male teachers and female teachers both like Cooperative Learning and Social Affective teaching strategies, where teachers utilize collaboration between students and emphasize the socio-emotional aspects of students during the learning process. However, it cannot be denied that challenges such as the lack of physical and non-physical school resources can affect the implementation of certain strategies. The findings are expected to be a reference for the development of teacher training programs and for improving the quality of English teaching in schools.